Cognitive-behavioural therapy for ADHD in adolescents and adults a psychological guide to practice - Young, Susan, 1957- (Wiley-Blackwell, 2012)
"The first edition of this book introduced the Young-Bramham Programme, a pioneering approach to cognitive behavioural treatment for ADHD in adults, which was well-received by clinical and academic communities alike. Based on the latest findings in the field, the authors have expanded the second edition to incorporate treatment strategies not only for adults, but also for adolescents with ADHD. Updates the proven Young-Bramham Programme to be used not only with adults but also with adolescents, who are making the difficult transition from child to adult services New edition of an influential guide to treating ADHD beyond childhood which encompasses the recent growth in scientific knowledge of ADHD along with published treatment guidelines Chapter format provides a general introduction, a description of functional deficits, assessment methods, CBT solutions to the problem, and a template for group delivery Provides a wealth of downloadable assessment checklists and tools"--